2003
DOI: 10.1046/j.1432-1033.2003.03821.x
|View full text |Cite
|
Sign up to set email alerts
|

Fra‐1 targets the AP‐1 site/2G single nucleotide polymorphism (ETS site) in the MMP‐1 promoter

Abstract: The matrix metalloproteinase (MMP) family degrades the extracellular matrix. One member of this family, MMP-1, initiates the breakdown of interstitial collagens. The expression of MMP-1 is controlled by the mitogen activated protein kinase (MAPK) pathway(s) via the activity of activator protein-1 (AP-1) and polyoma enhancing activity-3/ E26 virus (PEA3/ETS) transcription factors through consensus binding sites present in the promoter. Another ETS site in the MMP-1 promoter is created at )1607 bp by a single nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 54 publications
(82 reference statements)
5
37
0
2
Order By: Relevance
“…In A2058 melanoma cells, all haplotypes containing the À1607GG allele had significantly higher promoter activity than the haplotypes with the À1607G allele, which is in concordance with results from previous studies on the functional effect of the À1607GG>G polymorphism, whereas the other MMP1 gene promoter polymorphisms had not been taken into account (9,19). Furthermore, an important finding of our study is that in A2058 melanoma cells, there were significant differences among the six haplotypes that contain the À1607GG allele, such that the GG-…”
Section: Discussionsupporting
confidence: 90%
“…In A2058 melanoma cells, all haplotypes containing the À1607GG allele had significantly higher promoter activity than the haplotypes with the À1607G allele, which is in concordance with results from previous studies on the functional effect of the À1607GG>G polymorphism, whereas the other MMP1 gene promoter polymorphisms had not been taken into account (9,19). Furthermore, an important finding of our study is that in A2058 melanoma cells, there were significant differences among the six haplotypes that contain the À1607GG allele, such that the GG-…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, data from the literature suggest that fra-1 can modulate the expression of other MMPs after air pollutant exposure. Indeed, fra-1 has been shown to upregulate MMP-12 gene expression in the U937 human monocytic cell line [65], and to play a critical role in maintaining a high-level constitutive MMP-1 gene expression in melanoma cells [66]. Consistent with the study by ZHANG et al [63], MATSUZAKI et al [67] showed an increase in MMP-9 protein release from human neutrophils after incubation for 2 h with DEP extracts prepared on methanol.…”
Section: Mmp-9supporting
confidence: 66%
“…A limitation of our study was that we did not confirm whether this polymorphism was indeed functional. There is, however, ample supportive evidence establishing the functionality of this polymorphism in both normal stromal cells (Wyatt et al, 2002) and tumour cells, including melanoma (Tower et al, 2003a) and breast cancer cells (Tower et al, 2003b). These studies confirmed that cells containing a 2G allele displayed enhanced transcriptional activity compared to cells harbouring the 1G allele.…”
Section: Discussionmentioning
confidence: 90%